2015
DOI: 10.1080/21501203.2015.1110209
|View full text |Cite
|
Sign up to set email alerts
|

A new technique to monitor conidia of aquatic hyphomycetes in streams using latex-coated slides

Abstract: We examined the pattern of adherence of aquatic hyphomycetes conidia on six latex-coated slides (Artocarpus heterophyllus, A. hirsutus, Calotropis gigantea, Ficus benghalensis, Manilkara zapota and Plumeria rubra) with plain slides (control) exposed up to 18 h in a tropical coastal stream. Conidia of 21 species were trapped on latex-coated slides against seven on control slides. The total conidia adhered on latex-coated slides was higher than control slides. Latex-coated slides showed the highest diversity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…There is a notion that buoyancy as well as trapping efficiency of stauroid conidia in air bubbles (in foam) is better than that found for ovoid and scolecoid conidia (Iqbal and Webster 1973b). On the contrary, observations made in this study as well as in an earlier study (Ghate and Sridhar 2015) showed that water filtration, adhesion on plain slides and latex-coated slides are not biased towards conidial shape (Sridhar and Sudheep 2010; Ghate and Sridhar 2015). In this study, top five species in all methods encompass scolecoid as well as stauroid conidia; moreover, they were also top in frequency of occurrence based on annual or biannual observations in Konaje and Sampaje streams (with an exception of Trifurcospora irregularis in Konaje stream).…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…There is a notion that buoyancy as well as trapping efficiency of stauroid conidia in air bubbles (in foam) is better than that found for ovoid and scolecoid conidia (Iqbal and Webster 1973b). On the contrary, observations made in this study as well as in an earlier study (Ghate and Sridhar 2015) showed that water filtration, adhesion on plain slides and latex-coated slides are not biased towards conidial shape (Sridhar and Sudheep 2010; Ghate and Sridhar 2015). In this study, top five species in all methods encompass scolecoid as well as stauroid conidia; moreover, they were also top in frequency of occurrence based on annual or biannual observations in Konaje and Sampaje streams (with an exception of Trifurcospora irregularis in Konaje stream).…”
Section: Discussioncontrasting
confidence: 73%
“…Considering adhesion property of conidia, a variety of techniques have been designed for assessment of aquatic hyphomycetes (e.g. cellophane, collodion-coated glass rods, latex-coated slides, plexiglass and rosin-coated slides) (Webster 1959; Lindsey and Glover 1976; Müller-Haeckel and Marvanová 1976; Bärlocher et al 1977; Ghate and Sridhar 2015). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations